Path coefficient analysis of environmental factors influencing flight activity of Apis florea F. and seed yield in carrot (Daucus carota L.) - Abrol, D. P. (International Journal of Horticultural Science, 2004)
Foraging ecology of insect pollinators visiting carrot flowers (Daucus carota L.) was studied in relation to five environmental variables. The dwarf honeybee, Apis florea L., was the most abundant flower visitors and comprised more than 94% of the total flower visiting insects. Commencement of flight activity occurred when a minimum threshold of environmental variables was surpassed while the cessation was governed mainly by decline in values of light intensity and radiation. In between the commencement and cessation, the foraging population correlated significantly and positively with air temperature, light intensity, solar radiation and nectar-sugar concentration and negatively with relative humidity. Path coefficient analysis, however, revealed that direct effect of temperature was high and positive followed by light intensity and solar radiation while the direct effect of relative humidity was high and negative. The direct effect of nectar-sugar concentration was negative and negligible. Evidently, path coefficient analysis gave a more clear picture of effects than did the simple correlation analysis. Apis florea on an average visited 1.14+0.23 and 22.78+2.57 umbels and flowers/min, respectively during different hours of the day. Furthermore, the insect pollinated plots produced significantly more seeds with heavier weights than those isolated from insect visits.